1997
DOI: 10.1001/archneur.1997.00550160019010
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Characteristics of the Syndrome of Mesial Temporal Lobe Epilepsy

Abstract: Distinct neuropsychological features of spared, compromised, and laterality-specific cognitive impairments characterize the syndrome of MTLE. This information needs to be incorporated into formal syndrome criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
253
8
21

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 422 publications
(312 citation statements)
references
References 40 publications
24
253
8
21
Order By: Relevance
“…The clinical relevance of these findings, at this point, can only be speculative. Nevertheless, it is widely known that patients with L‐MTLE have worse cognitive performance than R‐MTLE [Alessio et al, 2006; Hermann et al, 1997]. As also suggested by intracranial EEG studies, the abnormal connectivity in the hemisphere contralateral to the epileptogenic zone in L‐MTLE could be an attempt to compensate the functional deficit, as the performance of working memory scores have been correlated to this increased contralateral connectivity [Bettus et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical relevance of these findings, at this point, can only be speculative. Nevertheless, it is widely known that patients with L‐MTLE have worse cognitive performance than R‐MTLE [Alessio et al, 2006; Hermann et al, 1997]. As also suggested by intracranial EEG studies, the abnormal connectivity in the hemisphere contralateral to the epileptogenic zone in L‐MTLE could be an attempt to compensate the functional deficit, as the performance of working memory scores have been correlated to this increased contralateral connectivity [Bettus et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…FSIQ has not previously been shown to be a significant predictor of memory outcome after ATL. Because lower preoperative FSIQ score is associated with earlier age at onset and the presence of HS (20,48), lower FSIQ may be expected to predict memory stability after ATL. The finding of a positive predictive relationship between preoperative FSIQ and postoperative memory score therefore seems unusual.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally acknowledged that memory functioning is the primary cognitive morbidity in TLE and is related to the functional adequacy of the hippocampus. Nevertheless, it is also evident that there is a more diffuse disruption of cognition in unilateral TLE (Glosser et al, 1997;Helmstaedter et al, 2003;Hermann et al, 1997) and that there is considerable heterogeneity in cognitive dysfunction among patients with unilateral TLE (Oyegbile et al, 2004). We have previously suggested that abnormalities outside the affected hippocampus and temporal lobe may contribute to nonmemory cognitive impairment (Hermann et al, 2003).…”
Section: Cognitive Functioningmentioning
confidence: 99%
“…Affected brain structures include temporal lobe structures adjacent and closely linked to the hippocampus such as the amygdala and entorhinal cortex (Bernasconi et al, 2005;Moran et al, 2001), as well as extratemporal lobe structures such as the thalamus and basal ganglia (Bonilha et al, 2005;Dreifuss et al, 2001;Natsume et al, 2003). Cognitive impairment in TLE has also been shown to encompass domains other than episodic memory, including intellectual functioning, language, executive functioning, visual perceptual functions, and motor abilities (Glosser et al, 1997;Hermann et al, 1997;Marques et al, 2007;Martin et al, 2000;Oyegbile et al, 2004). These findings raise the possibility that the broader pattern of cognitive impairment in TLE is associated with brain abnormalities in regions outside the temporal lobe.…”
Section: Introductionmentioning
confidence: 99%